Melastoma malabathricum as a Natural Antioxidant Modulator: A Systematic Review of Its Molecular Mechanisms in Reducing Reactive Oxygen Species - Vega, Nadia; Amin, Azizah; Anami Riastri (Universitas Muhammadiyah Malang, 2026)
Melastoma malabathricum L. (MM) exhibits antioxidant potential, reducing oxidative stress caused by free radicals, as demonstrated by various research methods, including phytochemical, in vitro, and in vivo tests. This study aims to compile a comprehensive review of the scientific literature on the phytochemical profile and antioxidant activity of MM, as well as its mechanism of action in suppressing oxidative stress. The research method employed a review, with searches conducted in databases such as ScienceDirect, Scopus, and PubMed. The articles were then systematically selected according to PRISMA guidelines. The screening criteria included full-text articles published in English between 2016 and 2025, focusing on original research relevant to the antioxidant properties of MM. A total of 40 articles were deemed eligible after screening. MM shows potential as a natural antioxidant, with the most bioactive compounds being flavonoids such as quercetin and kaempferol. In vivo tests showed increases in enzymatic and non-enzymatic antioxidant systems, accompanied by decreases in oxidative stress biomarkers such as MDA, and modulation of key molecular pathways involving nitric oxide (NO). These results support the potential of MM in preventing oxidative stress associated with degenerative diseases.